Diversity Of Fusarium Species Associated With Bakanae Disease Of Rice In Malaysia And Indonesia - Mohd Zainudin, Nur Ain Izzati (2007)
Many diseases were reported to be associated with rice; one of the diseases is bakanae that caused by Fusarium spp .. The main objective of these studies was to characterize Fusarium spp. in Section Liseola isolated from bakanae-infected rice in Malaysia and Indonesia by using several approaches in order to determine the similarities and variabilities between the species. Results during sampling bkanae disease were widespread in Peninsular Malaysia and three provinces in Indonesia (East Java, Padang and Samarinda) except in Yan, Kedah.